Mixed Convection Heat Transfer in 2D Lid Driven Filled with Newtonian Fluid - Siti Nurmaizatul Ain Nasran,; Muhamad Ghazali Kamardan, (Enhanced Knowledge in Sciences and Technology, 2024)
The study of mixed convection heat transfer in a 2D lid driven filled with Newtonian fluid and insulated horizontal walls has been performed. COMSOL Multiphysics used to solve the problem by visualizing the streamlines and isotherms. The study considered parameters such as Prandtl, Rayleigh, and Peclet numbers, along with Dirichlet boundary conditions. When the Peclet number increases, streamlines near the moving walls become less visible, showing that advection has replaced buoyancy as the main force. At the same time, isotherms start tilting towards the vertical walls because temperature differences near the boundaries are increasing.